Identifikasi Bahaya Dan Penilaian Risiko Di Stasiun Boiler Menggunakan Metode Hirarc Di Pt.Kim Nagan Raya - Purba Siboro, Ester Yunisara; Darmawan, Darmawan; Nabela, Danvil; is, Jun Musnadi; Sriwahyuni, Susy (An Idea Health Journal, 2024)
Hazard identification and risk assessment to prevent it accident Work on operator. The aim of this research is to identify risk hazards at boiler stations using the HIRARC method at PT Sawit. This type of research is qualitative in nature which uses a natural setting for the purpose of interpreting phenomena that occur and is carried out by being involved in finding narrative images that give rise to the impact of a person's actions. The research was conducted at PT. Sawit, Nagan Raya Regency on 5 informants, of which the main informants were 3 operators at the Boiler Station, 1 person Health Safety Environment (HSE) as key informant, and 1 process assistant as supporting informant. Technique collection data done with observation And interview in-depth, data analysis using the HIRARC method Research results obtained from risk assessment use method HIRARC with table Risk Matrix so presentation risk moderate, namely 60%, is categorized as moderate, low risk presentation, namely 20%, is categorized as low, and high risk presentation, namely 20%, is categorized as high. The conclusion of the research is that at the Boiler Station, it was found that there were work accidents at a medium level of 60% while at a low level it was 20%, and at a high level it was only 20%, so it can be concluded that there were indication work accident occurs, and will increases if Boiler Station operators do not use Personal Protective Equipment (PPE).